Pengembangan Modul Kerja Ergonomis dengan Pendekatan pada Komunitas Pengrajin Anyaman Daun di Kabupaten Jombang - Putri Ayuni Alayyannur; Bian Shabri Putri Irwanto; Shinta Arta Mulia; Addien Nadira; Muhammad Iqbal Ridho Maulana Arifin (Lembaga Pengembangan Kinerja Dosen, 2026)
Introduction: Pandan leaf weaving artisans in Jombang Regency are part of the creative economy sector that contributes to community welfare. However, their work is still dominated by non-ergonomic postures, traditional tools, and less supportive environments, increasing the risk of musculoskeletal disorders and reducing productivity.Objective: This activity aims to develop and implement a community-based ergonomic work module to improve artisans’ knowledge, attitudes, and practices, as well as to empower Occupational Health Effort Post (Pos UKK) cadres as agents of change.Methods: A participatory approach was used through preparation, implementation, and monitoring and evaluation stages. Activities included training Pos UKK cadres in ergonomic workstation development and public speaking, training artisans in ergonomic practices, and developing educational media such as X-banners, pocket books, hand fans, and videos. Evaluation used pre-test and post-test to measure knowledge changes.Results: Most respondents had basic to intermediate education levels and long work experience. The Wilcoxon test showed a significant increase in knowledge after the intervention, with 58 of 60 respondents improving their post-test scores. A p-value of 0.000 (p < 0.05) indicates a significant positive effect of the intervention.Conclusion: The community-based ergonomic work module effectively improves artisans’ knowledge of ergonomic principles. This approach, along with the involvement of Pos UKK cadres, supports sustainable implementation, reducing musculoskeletal risks and improving comfort and productivity.